Quick Response Anti-Theft Measures in Jewelry Stores and Banks Utilizing the Internet of Things - Widodo, Sarono; Bramantyo, Hutama Arif; Wardihani, Eni Dwi; Yulianto, Taufiq; Helmy, Helmy; Wasito, Endro; Daffa, Muhammad; Yuliana, Lutfi (Politeknik Negeri Semarang, 2024)
The act of theft is a prevalent criminal activity within society, particularly observed in financial institutions and jewelry establishments, owing to the significant economic worth associated with valuable assets like currency, gold, and diamonds. Certain locations lack an integrated security system that interfaces with law enforcement, hence posing challenges for victims to report criminal incidents, particularly in cases involving armed or violent attackers. Hence, the purpose of this final project tool is to streamline and expedite theft reporting by leveraging the capabilities of the Internet of Things. This tool gathers empirical data in the form of visual representations, geographical coordinates, and temporal information pertaining to an incident. The development process employs the waterfall methodology, characterized by an average data transmission speed of 21.5 seconds and a database-to-telegram latency time of around 3.85 seconds. The complete duration encompassing the stages of detection and subsequent notification via telegram amounts to approximately 25.35 seconds. The test results indicate a location tolerance of around 5-10 meters relative to the test spot.